Biological markers of endothelial dysfunction and fibrosis, macro- and microcirculation alterations in patients with obstructive and nonobstructive coronary artery disease and diabetes mellitus. (14th October 2021) - Iusupova, A O; Pakhtusov, N N; Kozhevnikova, M V; Belenkov, Y U N; Privalova, E V
Abstract: Aim of the study: To analyze the association of biological markers levels of endothelial dysfunction and fibrosis with macro- and microcirculation alterations in patients with obstructive and nonobstructive coronary artery disease (CAD) and type 2 diabetes mellitus (DM). Methods: 52 patients with CAD were enrolled and divided into 4 groups: 19 patients with nonobstructive CAD (1–49% stenosis) without DM (1 group: 4 men, age 64.89±7.61, body mass index (BMI) 28.14±3.69 kg/m 2 ); 13 patients with obstructive CAD (≥50% stenosis) without DM (2 group: 9 men, age 66.92±7.02, BMI 30.4±5.91 kg/m 2 ); 10 patients with obstructive CAD (3 group: 4 men, age 63.4±10.37, BMI 31.7±4.81kg/m 2 ) and 10 patients with nonobstructive CAD with DM (4 group: 3 men, age 64.6±5.32, BMI 33.74±3.25 kg/m 2 ). Patients were matched for age, sex and BMI. All patients underwent coronary angiography or coronary computed tomography angiography. Biological markers levels (E-selectin, ng/ml; tissue inhibitor of metalloproteinase 1 (TIMP-1), ng/ml) were measured using ELISA. To determine arterial damage in both macro- and microcirculation, digital reactive hyperemia photoplethysmography were performed. Endothelial function of small (Occlusion Index, OI) and large vessels (Phase Shear, PS, ms) were analyzed. Vascular remodeling of aorta (Stiffness Index, aSI, m/s) and arterioles (Reflection Index, RI, %) were studied. Results: The elevation of E-selectin (1 – 21.6 [18.7; 30.4]; 2 – 31.5 [20.1; 36.9]; 3 – 42.25 [29.9; 55.3]; 4 – 42.1 [33.1; 46.5]) and TIMP-1 (1 – 416 [376; 481]; 2 – 478 [381; 539]; 3 – 534 [490; 579]; 4 – 590 [520; 782]) levels were found in all groups. Statistical analysis revealed significant differences between TIMP-1 (p1–3=0.004; p1–4=0.003) and E-Selectin (p1–3=0.013; p1–4=0.01) levels. Remodeling of large vessels was detected only in patients with obstructive CAD without DM and nonobstructive CAD with DM (2 – aSI, 9.05 [7.08; 10.58]; 3 – aSI, 8.2 [7.6; 11]). Patients in all groups had endothelial dysfunction of large vessels (PS, 1 – 5.1 [1.75; 7.75]; 2 – 6.45 [5.53; 9.03]; 3 – 7.65 [13.4; 9.5]; 4 – 4.6 [0.7; 8.1] and arterioles (IO; 1 – 1.5 [1.38; 1.78]; 2 – 1.4 [1.26; 1.53]; 3 – 1.4 [1.2; 1.7]; 4 – 1.3 [1.2; 2.0]). Structural disorders of arterioles were found in all groups, except for patients with obstructive CAD without DM (RI, 1 – 36.95 [23.4; 52.65]; 2 – 28.25 [23.35; 53.75]; 3 – 41.15 [26.5; 55]; 4 – 44.7 [20; 54.5]. The data did not show significant differences between the study groups. Conclusions: The data showed that biological markers levels of endothelial dysfunction and fibrosis were increased in all groups. Significant differences revealed between the levels of E-selectin and TIMP-1 in patients with nonobstructive CAD without DM and patients with CAD and DM, regardless of the degree of stenosis. All patients had functional changes of large vessels and arterioles regardless of the severity of coronary artery atherosclerosis and presence of DM. Funding Acknowledgement: Type of funding sources: None.